Perbaikan Kelarutan Albendazol Melalui Pembentukan Kristal Multikomponen dengan Asam Malat: Improvement of Albendazole Solubility Through Multicomponent Crystal Formation with Malic Acid - Alatas, Fikri; Abdul Azizsidiq, Fahmi; Hartyana Sutarna, Titta; Ratih, Hestyari; Nurono Soewandhi, Sundani (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2020)
An effort to improve the solubility of albendazole (ABZ), an anthelmintic drug has been successfully carried out through the formation of multicomponent crystal with dl-malic acid (MAL). Construction of phase solubility curve of ABZ in MAL solution and crystal morphological observations after recrystallization in the acetone-ethanol (9:1) mixture were performed for initial prediction of multicomponent crystal formation. ABZ-MAL multicomponent crystal was prepared by wet grinding or also known as solvent-drop grinding (SDG) with acetone-ethanol (9:1) mixture as a solvent followed by characterization of the multicomponent crystal formation by powder X-ray diffraction and Fourier transform infrared (FTIR) methods. The solubility of ABZ-MAL multicomponent crystal was tested in water at ambient temperature and in pH 1.2, 4.5 and 6.8 of buffered solutions at 37Â°C. The phase solubility curve of the ABZ in the MAL solution showed type Bs. The ABZ-MAL mixture has a different crystalline morphology than pure ABZ and MAL after recrystallization in the acetone-ethanol mixture (9:1). The powder X-ray diffraction pattern and the FTIR spectrum of ABZ-MAL from SDG different from intact ABZ and MAL powder X-ray diffraction patterns and these results can indicate the ABZ-MAL multicomponent crystal formation. The ABZ-MAL multicomponent crystal has better solubility than pure ABZ in all media used. These results can be concluded that ABZ-MAL multicomponent crystal can be prepared by solvent-drop grinding method with acetone-ethanol (9:1) mixture as a solvent and can increase the solubility of albendazole.